2021
DOI: 10.24193/jebp.2021.2.18
|View full text |Cite
|
Sign up to set email alerts
|

"Pandemic Dreams are Susceptible to Priming and Unrelated to COVID-19 Exposure"

Abstract: "Surveys that have recruited participants through social media and news websites have led researchers and clinicians to conclude that the COVID-19 pandemic has precipitated a parallel pandemic of nightmares that reflect pandemic-induced psychological distress. Many of these surveys were administered to participants who intentionally opted into research knowing that the investigators were soliciting pandemic dream reports. This investigation surveyed 193 college students who were blind to the purpose of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Although post‐traumatic stress disorder (PTSD) symptoms accessed through self‐report measures in the general population were associated with an increase in DRF in one study (Gorgoni et al, 2021 ), there were contradictory findings in the relationship between DRF, psychological distress and COVID‐19‐related variables emerging in eight studies (Conte et al, 2022 ; Fränkl et al, 2021 ; Gallagher & Incelli, 2021 ; Scarpelli, Alfonsi, D'Anselmo, et al, 2021 ; Scarpelli, Alfonsi, Gorgoni, et al, 2021 ; Schredl & Bulkeley, 2020 ; Solomonova et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although post‐traumatic stress disorder (PTSD) symptoms accessed through self‐report measures in the general population were associated with an increase in DRF in one study (Gorgoni et al, 2021 ), there were contradictory findings in the relationship between DRF, psychological distress and COVID‐19‐related variables emerging in eight studies (Conte et al, 2022 ; Fränkl et al, 2021 ; Gallagher & Incelli, 2021 ; Scarpelli, Alfonsi, D'Anselmo, et al, 2021 ; Scarpelli, Alfonsi, Gorgoni, et al, 2021 ; Schredl & Bulkeley, 2020 ; Solomonova et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in dreaming were greater in women than man. During the pandemic, women showed a major increase in COVID‐19‐related dream frequency (four studies) (Barrett, 2020 ; Guerrero‐Gomez et al, 2021 ; Parrello et al, 2021 ; Schredl & Bulkeley, 2020 ), NF (nine studies) (Currie, 2021 ; Drager et al, 2022 ; Goncalves et al, 2022 ; Guerrero‐Gomez et al, 2021 ; Kilius et al, 2021 ; Lehman et al, 2021; Parrello et al, 2021 ; Scarpelli, Alfonsi, D'Anselmo, et al, 2021 ; Scarpelli, Alfonsi, Gorgoni, et al, 2021 ), negative emotions and emotional intensity of dreams (seven studies) (Barrett, 2020 ; Conte et al, 2022 ; Gorgoni et al, 2021 ; Iorio et al, 2020 ; Parrello et al, 2021 ; Schredl & Bulkeley, 2020 ; Sommantico et al, 2021 ), and DRF (eight studies) (Fränkl et al, 2021 ; Gallagher & Incelli, 2021 ; Giovanardi et al, 2022 ; Guerrero‐Gomez et al, 2021 ; Iorio et al, 2020 ; Parrello et al, 2021 ; Scarpelli, Alfonsi, Gorgoni, et al, 2021 ; Sommantico et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, especially people who already had a change in dream and nightmare frequency as well as dream content could have chosen to participate in these studies which focused on dreams and COVID-19. However, the study by Callagher and Incelli [ 9 ] tested especially whether this sort of self-selecting bias leads to an overestimation of the changes in dream and nightmare frequency and dream content, or even creates the described changes in the first place. They did not give their participants any information about the purpose of the study until participation and yet they still found the described changes.…”
Section: Discussionmentioning
confidence: 99%
“…In a study a little later, conducted in Brazil between May and June 2020, about 33% of the participants reported dreams about COVID-19 [ 23 ]. In a more recent American study that took place in the fall of 2020, the proportion of dream reporters, who had a dream about COVID-19 increased to 45–65% [ 9 ]. Dream content also seems to change as the pandemic progresses.…”
Section: Impact On Dreamsmentioning
confidence: 99%
“…According to those theoretical frameworks, findings in the literature of dream studies on populations subject to the COVID-19 lockdown measures (e.g., Borghi et al, 2021; Cong et al, 2022; Gallagher & Incelli, 2021; Guo & Shen, 2021; Iorio et al, 2020; Kilius et al, 2021; Margherita et al, 2021; Mariani, Gennaro, et al, 2021; Mariani, Monaco, et al, 2021; Marogna et al, 2021; Mota et al, 2020; Parrello & Sommantico, 2022) have shown that the isolation-quarantine situation has a strong impact on dreaming. More specifically, several studies indicated the impact of the COVID-19 pandemic on dream and nightmare recall frequency (e.g., Alghamdi et al, 2022; Conte et al, 2022; Fränkl et al, 2021; Giovanardi et al, 2022; Gorgoni et al, 2021; Gorgoni, Scarpelli, Alfonsi, & De Gennaro, 2022; Guerrero-Gomez et al, 2021; Guo & Shen, 2021; Kennedy et al, 2022; Margherita et al, 2021; Musse et al, 2020; Parrello et al, 2021; Scarpelli et al, 2021; Schredl & Bulkeley, 2020; Schredl et al, 2022; Solomonova et al, 2021; Sommantico, Iorio, Lacatena, & Parrello, 2021), as well as on dream and nightmare content and emotion.…”
Section: The Current Study: Aims and Hypothesesmentioning
confidence: 99%